Stella Vladimirovna Vassilenko (1936−2011): in memoriam - Petryashov, Victor V.; Daneliya, Mikhail E.; Chernyshev, Alexey V. (Zootaxa, 2011)
Stella Vladimirovna Vassilenko—Russian zoologist, carcinologist, biogeographer, prominent specialist in amphipods, particularly skeleton shrimps (Caprellida), hooded shrimps (Cumacea) and crabs (Decapoda: Brachyura) of cold and moderate waters of the World Ocean; author and co-author of 6 families and subfamilies, several genera and many crustacean species.